2011
DOI: 10.1051/kmae/2011019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of constant and stepwise changes in temperature on the species abundance dynamics of four cladocera species

Abstract: Key-words:temperature, ecological optimum, Cladocera, stepwise changes, prolonged effects, realized niche Laboratory experiments with natural zooplankton communities were carried out to study the effects of two contrasting temperature regimes: constant temperature (15, 20, and These results support the previously formulated hypothesis that, in determining the ecological temperature optimum of a species within a natural community, it is not enough to define its optimum from constant, cyclic or random temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Reduced diversity and dominance of bloom-forming species including Cyanobacteria may also alter dietary availability and nutritional quality for consumers. Recent experimental evidence suggests that temperature effects on grazers seem to be mostly compromised by resource availability and its biochemical composition (Verbitsky & Verbitskaya, 2011). For example, the filter feeding Daphnia decreased the magnitude of spring peak in response to changes in algal composition (Winder et al, 2012) and reduced algal carrying capacity (Schalau, Rinke, Straile, & Peeters, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced diversity and dominance of bloom-forming species including Cyanobacteria may also alter dietary availability and nutritional quality for consumers. Recent experimental evidence suggests that temperature effects on grazers seem to be mostly compromised by resource availability and its biochemical composition (Verbitsky & Verbitskaya, 2011). For example, the filter feeding Daphnia decreased the magnitude of spring peak in response to changes in algal composition (Winder et al, 2012) and reduced algal carrying capacity (Schalau, Rinke, Straile, & Peeters, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The species Ch. sphaericus occurs in a wide range of pH and temperatures from 2°C to 4°C – functioning without reproduction (Rivier, 1992, 2005) to 36°C (Gorobey, 1974; Verbitsky and Verbitskaya, 2011). Laboratory tests show that at temperatures above 25°C the mortality of individual Chydorus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations of D . longispina under natural conditions in a temperate zone indicated that this species became highly abundant at temperatures above 14°C, and their favourable temperature range was 15–21°C [ 57 ]. In terms grouped in sub-cluster ESp (“early spring”), the temperature reached a median of 13.86°C.…”
Section: Discussionmentioning
confidence: 99%